DIABETES - SYSTEMIC INVOLVEMENT IN ORAL HEALTH LITERACY AT PATIENTS WITH PERIODONTITIS. REVIEW - Dora Popescu; Dorin Gheorghe; Iren Moraru; Ana Maria Rȋca; Cristina Berechet; Camelia Maglaviceanu; Lucian Dragomir (Romanian Dental Association for Education, 2019)
Understanding of association between oral health literacy and periodontal disease is an important objective for the health of patients. Any factor that involves periodontal changes may influence the patient's oral health status. The condition of the periodontium is of major importance for oral health because it is the essential condition for good and long-lasting dentistry on dental arches